PENGARUH LAYANAN DROP BOX DAN E-FILING TERHADAP TINGKAT KEPATUHAN PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PAJAK PENGHASILAN - Nugroho, Dimas Andri Dwi (Jurnal Mahasiswa Perpajakan, 2014)
Tax is a potential revenue that became the main priority and still very potentially improved its contribution. In order to increase the revenue from the tax sector, much needed awareness as well as enthusiastic taxpayers as tax payers. The purpose of this study is: to know and to test the drop box service and e-filing simultaneously and partial delivery compliance levels affect the annual income tax (PPh), tax return (SPT) and to know the variables that influence the level of compliance against the dominant. The type of research used in this research is explanatory research. Sample of respondents that taxpayer listed on the Tax Service Report (KPP) Pratama Pare who are already utilizing the facilities services drop box and e-filing. The method used is the sample of accidental sampling. Analysis of the method used is descriptive Analysis and Multiple Linear Analysis. From the results of the study could note that the variable drop box and e-filing in effect simultaneously against compliance filing Annual income tax. From the results of the analysis of partially known that e-filing variable has contributed to the Annual income tax filing compliance SPT. Variable e-filing is the dominant variables affect the compliance of delivery SPT Annual PPh. Advice from research results should continue to improve outreach the Directorate General of Taxation (DJP) regarding taxation applicable and continue to provide routine socialization. Keywords: Drop box, E-filing, and the Compliance submission of Annual SPT PPh